PEMANFAATAN TUMBUHAN SUMBER PANGAN DI DESA SETIA JAYA KECAMATAN TERIAK KABUPATEN BENGKAYANG - Kristina, Mega; Manurung, Togar Fernando; Sisillia, Lolyta (Universitas Tanjungpura, 2020)
The research objective was to determine the plant food sources used by the people of Setia Jaya Village, Teriak District, Bengkayang Regency. The research was conducted on 11 April 2019 - 9 May 2019. The research method used a survey method, while the interviews were conducted using a snowball sampling technique. Based on the research conducted, 50 plant species were found with 28 types of families, namely Anarcaceae, Verberanaceae, Oxalidaceae, Moraceae, Malvaceae, Euphorbiaceae, Myrtaceae, Fabaceae, Auriculariaceae, Sapindaceae, Melastomataceae, Bromeliaceae, Annonaceae, Poaceae, Arecaceae, Piperceae, Meliaceae, Passifloraceae, Zigiberaceae, Solanaceae, Robiaceae, Dryopteriaceae, Gnetaceae, Blechnaceae, Schizophyllaceae, Caricaceae, Tricholomataceae and Bombaceae. Food source plants have use values as follows: mango, star fruit, durian, rubber, papaya, koko, red fern, green fern, jackfruit, soursop, petai, bamboo shoots and cassava as much as 1, starfruit, bebuas, cempedak, as much as durian kawai. 0.966667, Lingkodok as much as 0.766667, durian kawai as much as 0.966667, water guava, taro, melinjo, and mentawa as much as 0.6, guava as much as 0.7, kedondong and langsat as much as 0.666667, longan and purple eggplant 0.63333, candlenut as much as 0.233333, white mushrooms as much as 0.266667, fungus and ear mushrooms as much as 0.2, kelampai and pineapple as much as 0.3, areca as much as 0.933333, sago as much as 0.366667, pepper, salak and bay leaves as much as 0.5, lelatup as much as 0.166667, betel and breadfruit as much as 0.466667, tamarind eggplant as much as 0.566667 and ciplukan as much as 0.4.Keywords: Food Plants, Tembawang Forest, Utilization